2022
DOI: 10.2196/29250
|View full text |Cite
|
Sign up to set email alerts
|

Community Mental Health Clinicians’ Perspectives on Telehealth During the COVID-19 Pandemic: Mixed Methods Study

Abstract: Background In March 2020, a rapid shift to telehealth occurred in community mental health settings in response to the need for physical distancing to decrease transmission of the virus causing COVID-19. Whereas treatment delivered over telehealth was previously utilized sparingly in community settings, it quickly became the primary mode of treatment delivery for the vast majority of clinicians, many of whom had little time to prepare for this shift and limited to no experience using telehealth. Lit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 62 publications
2
18
0
2
Order By: Relevance
“…As prior reports have suggested, speedy innovation is often lacking impact analysis but should be considered at a later stage if innovations are to stay ( 14 ). Although accessibility of services was increased for some, switching to one hundred percent telehealth mode illuminated inequities – not everybody had equal access to internet, data, or even hardware; not everybody – both service users and staff – had a safe, confidential, and professional environment for an online consultation, similar to what has been reported in other studies ( 23 , 24 ). Telehealth varied in effectiveness depending on types of presentation.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…As prior reports have suggested, speedy innovation is often lacking impact analysis but should be considered at a later stage if innovations are to stay ( 14 ). Although accessibility of services was increased for some, switching to one hundred percent telehealth mode illuminated inequities – not everybody had equal access to internet, data, or even hardware; not everybody – both service users and staff – had a safe, confidential, and professional environment for an online consultation, similar to what has been reported in other studies ( 23 , 24 ). Telehealth varied in effectiveness depending on types of presentation.…”
Section: Discussionsupporting
confidence: 56%
“…Consequently, many providers noted that while innovation was needed and some of it has proven to be effective, as we are settling in to a “new normal” we need a more nuanced discussion about what works and what does not, and what improvements can be made. Prior qualitative evidence echoes these observations with mental health workforce embracing telehealth because of its scheduling flexibility and increase in attendance from service users, but noting potential inequities for service users and potential negative effects on one’s job satisfaction and wellbeing ( 23 ). Our results contribute to the literature emphasising the need to consider hybrid solutions between face-to-face care and telehealth and more flexible working environments where online work is a choice rather than a necessity.…”
Section: Discussionmentioning
confidence: 99%
“…For example, some providers reported that eye movement desensitization and reprocessing (EMDR) therapy was challenging to conduct remotely ( Freske and Malczyk, 2021 ), with one provider stating that they attempted to teach their patient how to perform this therapy on themselves ( Schow et al, 2022 ). Some providers reported that they would have liked to have received training and education on how to effectively deliver care remotely ( Schriger et al, 2022 ), while others felt confident in their abilities and did not feel there was a need for training ( Budhwani et al, 2021 ). In contrast, phone consultations were acknowledged as an effective and efficient method for some appointments such as medication visits ( Budhwani et al, 2021 ; Wyler et al, 2021 ) and brief follow-up calls ( Christensen et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have investigated the implementation of telehealth platforms during the pandemic (Olszewski et al, 2022; [25] ). Multiple factors were identified to pose significant challenges, including cost, data privacy, the digital divide, and training programs on the adoption and utilization of telehealth services.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, challenges and barriers to enabling telehealth services can affect a patient's decision on future selection for the type of visit to receive healthcare services. Factors such as accessibility, mitigating barriers, effective technology, and training programs were crucial in facilitating the utilization of telehealth [25] . However, clinicians' and patients’ perspectives toward telehealth can vary depending on facilities' accessibility and barriers.…”
Section: Introductionmentioning
confidence: 99%